Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Population-specific transcriptomics of Pacific oyster after exposure to a highly pathogenic, globally distributed virus - Bernarda Calla; Neil F. Thompson; Colleen A. Burge (Fish & Shellfish Immunology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Pedigree-based genome-wide imputation using a low-density amplicon panel for the highly polymorphic Pacific oyster Crassostrea (Magallana) gigas - Ben J.G. Sutherland; Konstantin Divilov; Neil F. Thompson; Thomas A. Delomas; Spencer L. Lunda; Christopher J. Langdon; Timothy J. Green (Aquaculture, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Evaluating a new population of Kumamoto oysters (Crassostrea sikamea) for breeding on the U.S. Pacific coast - Chris Langdon; Claudio Manoel Rodrigues de Melo; Konstantin Divilov; Blaine Schoolfield; Noah Merz; Neil Thompson (Aquaculture, 2025)

Implementing circular business models in linear economic systems: The case of a new venture addressing the embeddedness paradox - Amba Maria van Erkelens; Koen van Bommel; Katinka J.P. Quintelier; Neil Aaron Thompson; Michiel Verver (Journal of Cleaner Production, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Assessing selection potential for Pacific oyster (Crassostrea gigas) to a North American OsHV-1 μvar: Comparing two experimental assay methods - Neil F. Thompson; M. Victoria Agnew; Bernarda Calla; Colleen A. Burge (Aquaculture, 2024)

Microhaplotypes generate higher breeding value accuracy compared to SNPs for imputation-based breeding strategies - Thomas A. Delomas; Christopher M. Hollenbeck; Joseph L. Matt; Neil F. Thompson (Aquaculture, 2024)

Sudden peak in tetrodotoxin in French oysters during the summer of 2021: Source investigation using microscopy, metabarcoding and droplet digital PCR - Laura Biessy; John K. Pearman; Kenneth Neil Mertens; Damien Réveillon; Véronique Savar; Philipp Hess; Hannah Hampton; Lucy Thompson; Luc Lebrun; Aouregan Terre-Terrillon; Kirsty F. Smith (Toxicon, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The mixed blessings of rare earth element supplements for tomatoes and ferns - Duc Huy Dang; Ashlyn Kernaghan; R.J. Neil Emery; Karen A. Thompson; Anna Kisiala; Wei Wang (Science of The Total Environment, 2024)

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Daily activity timing in the Anthropocene - Neil A. Gilbert; Kate A. McGinn; Laura A. Nunes; Amy A. Shipley; Jacy Bernath-Plaisted; John D.J. Clare; Penelope W. Murphy; Spencer R. Keyser; Kimberly L. Thompson; Scott B. Maresh Nelson; Jeremy M. Cohen; Ivy V. Widick; et al. (Trends in Ecology & Evolution, 2023)

‘Eye in the sky’: Off-the-shelf unmanned aerial vehicle (UAV) highlights exposure of marine turtles to floating litter (FML) in nearshore waters of Mayo Bay, Philippines - Neil Angelo S. Abreo; Remie M. Aurelio; Vladimer B. Kobayashi; Kirsten F. Thompson (Marine Pollution Bulletin, 2023)

Evaluating cost-effective genotyping strategies for genomic selection in oysters - Thomas A. Delomas; Christopher M. Hollenbeck; Joseph L. Matt; Neil F. Thompson (Aquaculture, 2023)

Conceptualizing a probabilistic risk and loss assessment framework for wildfires - Negar Elhami-Khorasani; Hamed Ebrahimian; Lawrence Buja; Susan L. Cutter; Branko Kosovic; Neil Lareau; Brian J. Meacham; Eric Rowell; Ertugrul Taciroglu; Matthew P. Thompson; Adam C. Watts (Natural Hazards, 2022)

Novel application of live imaging to determine the functional cell biology of endothelial-to-mesenchymal transition (EndMT) within a liver-on-a-chip platform - James Whiteford; Samantha Arokiasamy; Clare L. Thompson; Neil P. Dufton (In vitro models, 2022)
Objective Imaging endothelial cell behaviour under physiological conditions, particularly those associated with chronic fibrotic pathologies, is an incredibly challenging endeavour. While short-term assessments (hours) can be achieved with techniques such as intravital microscopy, vascular changes often occur over days and weeks which is unfeasible with current imaging techniques. These challenges are exemplified within the liver where liver sinusoidal endothelial cells (LSECs) are known to undergo dramatic changes termed endothelial-to-mesenchymal transition (EndMT) during fibrotic liver disease. Despite the established presence of EndMT in liver disease, the inaccessibility of viable liver tissue, and simplicity of 2D culture techniques has meant, the role of EndMT during disease progression remains largely undetermined. This study describes the development of novel fluorescent EndMT reporters to identify, track, and characterise the migratory behaviour of EndMT cells. We show that liver-on-a-chip (LOAC) platforms provide a flexible, optically accessible, and physiologically relevant microenvironment to study the vascular dynamics of EndMT during liver disease. Methods Identification, creation, and application of an EndMT-specific fluorescent reporter construct (EndMT-Rep). Transduction of EC using lentiviral packaged CNN1-eGFP construct as an inducible EndMT-Rep (CNN1-Rep) to 2D, 3D, and 4D imaging techniques for fixed and live cell imaging. Combined application of live and fixed imaging technologies to measure EndMT using CNN1-Rep on LOAC platform under physiological conditions. Demonstration of the high-resolution single-cell EndMT tracking by live cell time-lapse microscopy and with post-acquisition processing to perform a comparative study of CNN1-Rep and healthy LSECs within a NASH-like LOAC microenvironment. Conclusions LOAC enables prolonged, multi-platform imaging of endothelial cell sub-populations such as those undergoing EndMT in 2D and 3D cultures. Our study highlights the application of EndMT reporters, such as CNN1-Rep, to provide high-resolution imaging of EndMT behaviour for the first time under physiologically relevant liver microenvironment. Overall, these methods reveal the adaptability and impact of live-cell imaging on uncovering vascular behaviours, such as EndMT, that are unattainable in viable tissue or conventional 2D in vitro experiments.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Proteomic characterization of serum proteins from Atlantic salmon ( Salmo salar L.) from an outbreak with cardiomyopathy syndrome - Janina Z. Costa; Jorge del Pozo; Kevin McLean; Neil Inglis; Philippe Sourd; Andrei Bordeianu; Kim D. Thompson (Journal of Fish Diseases, 2021)
Cardiomyopathy syndrome (CMS), caused by piscine myocarditis virus (PMCV), is a serious challenge to Atlantic salmon ( Salmo salar L.) aquaculture. Regrettably, husbandry techniques are the only tool to manage CMS outbreaks, and no prophylactic measures are available at present. Early diagnosis of CMS is therefore desirable, preferably with non‐lethal diagnostic methods, such as serum biomarkers. To identify candidate biomarkers for CMS, the protein content of pools of sera (4 fish/pool) from salmon with a CMS outbreak (3 pools) and from clinically healthy salmon (3 pools) was compared using liquid chromatography–electrospray ionization–tandem mass spectrometry (LC‐ESI‐MS/MS). Overall, seven proteins were uniquely identified in the sera of clinically healthy fish, while 27 proteins were unique to the sera of CMS fish. Of the latter, 24 have been associated with cardiac disease in humans. These were grouped as leakage enzymes (creatine kinase, lactate dehydrogenase, glycogen phosphorylase and carbonic anhydrase); host reaction proteins (acute‐phase response proteins—haptoglobin, fibrinogen, α2‐macroglobulin and ceruloplasmin; and complement‐related proteins); and regeneration/remodelling proteins (fibronectin, lumican and retinol). Clinical evaluation of the suitability of these proteins as biomarkers of CMS, either individually or as part of a panel, is a logical next step for the development of early diagnostic tools for CMS.

Contribution of social media to cetacean research in Southeast Asia: illuminating populations vulnerable to litter - Amber Coram; Neil Angelo S. Abreo; Robert P. Ellis; Kirsten F. Thompson (Biodiversity and Conservation, 2021)
Litter in the marine environment, in particular plastic, is a significant threat to marine megafauna. Cetaceans are known to ingest or become entangled in marine debris, likely impacting individuals and populations. Southeast Asia is a biodiversity hotspot and harbours a diverse cetacean assemblage. However, there are key knowledge gaps relating to the impact of litter in this region due the lack of experts to survey its vast coastlines. This study aims to address such gaps by using social media, gathering data from Facebook posts relating to cetacean strandings and litter across Southeast Asia between 2009 and 2019. Results show that at least 15 cetacean species have been negatively affected by litter, with ingestion most commonly affecting deep-diving species. Epipelagic and mesopelagic foragers were most vulnerable to entanglement. Davao in the Philippines was identified as a litter-related stranding hotspot. The Irrawaddy dolphin ( Orcaella brevirostris ) and pygmy sperm whale ( Kogia breviceps ) are particularly vulnerable to litter. The combination of social media and peer reviewed literature can help build a more complete picture of the spatial distribution of marine litter and the scale of the impact it has on cetacean populations. In this study we provide details of a valuable online tool for helping to understand the impact of marine litter on cetaceans and other charismatic species that are a focus of community engagement.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Tolerance of wheat (Triticum aestivum) genotypes to root-lesion nematode (Pratylenchus thornei) in the subtropical grain region of eastern Australia - John P. Thompson; Jason G. Sheedy; Neil A. Robinson; Timothy G. Clewett (Euphytica, 2021)

Effects of temperature on sexual development in steelhead, Oncorhynchus mykiss - Kathleen S. Cole; David L. G. Noakes; Neil Thompson; Michael Blouin; Bruce Morrison; Ryan B. Couture; Joseph O’Neil; Carl B. Schreck (Environmental Biology of Fishes, 2021)

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

A Review of Overlapping Landscapes: Pseudoreplication or a Red Herring in Landscape Ecology? - Benjamin Zuckerberg; Jeremy M. Cohen; Laura A. Nunes; Jacy Bernath-Plaisted; John D. J. Clare; Neil A. Gilbert; Sofia S. Kozidis; Scott B. Maresh Nelson; Amy A. Shipley; Kimberly L. Thompson; André Desrochers (Current Landscape Ecology Reports, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Field Evaluation of Potato Genotypes for Resistance to Powdery Scab on Tubers and Root Gall Formation Caused by Spongospora subterranea - Francisco G. Bittara; Asunta L. Thompson; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2016)

Spawn date explains variation in growth rate among families of hatchery reared Hood River steelhead (Oncorhynchus mykiss) - Neil F. Thompson; Mark R. Christie; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2016)

Exosomes derived from endometriotic stromal cells have enhanced angiogenic effects in vitro - Djana Harp; Adel Driss; Sharifeh Mehrabi; Indrajit Chowdhury; Wei Xu; Dong Liu; Minerva Garcia-Barrio; Robert N. Taylor; Bert Gold; Samantha Jefferson; Neil Sidell; Winston Thompson (Cell and Tissue Research, 2016)

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Estimating surface NO2 and SO2 mixing ratios from fast-response total column observations and potential application to geostationary missions - T. Knepp; M. Pippin; J. Crawford; G. Chen; J. Szykman; R. Long; L. Cowen; A. Cede; N. Abuhassan; J. Herman; R. Delgado; J. Compton; et al. (Journal of Atmospheric Chemistry, 2015)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

Sex reversal, selection against hatchery females or wild males does not explain differences in sex ratio between first generation hatchery and wild steelhead, Oncorhynchus mykiss - Neil F. Thompson; Kathleen S. Cole; Laura A. McMahon; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2015)

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

The effects of extended intravenous nicotine administration on body weight and meal patterns in male Sprague–Dawley Rats - Patricia E. Grebenstein; Ian E. Thompson; Neil E. Rowland (Psychopharmacology, 2013)

Quantification of Field Resistance to Verticillium dahliae in Eight Russet-Skinned Potato Cultivars Using Real-Time PCR - J. S. Pasche; A. L. Thompson; Neil C. Gudmestad (American Journal of Potato Research, 2013)

Soil biotransformation of thiodiglycol, the hydrolysis product of mustard gas: understanding the factors governing remediation of mustard gas contaminated soil - Hong Li; Robert Muir; Neil R. McFarlane; Richard J. Soilleux; Xiaohong Yu; Ian P. Thompson; Simon A. Jackman (Biodegradation, 2013)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part II: future estimates - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part I: historical analysis - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Dakota crisp: A new high-yielding, cold-chipping potato cultivar with tablestock potential - Asunta L. Thompson; Bryce L. Farnsworth; Gary A. Secor; Neil C. Gudmestad; Duane Preston; Joseph R. Sowokinos; Marty Glynn; Harlene Hatterman-Valenti (American Journal of Potato Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Resistance to phytophthora erythroseptica and pythium ultimum in a potato clone derived from s. berthaultii and s. etuberosum - Asunta L. Thompson; Raymond J. Taylor; Julie S. Pasche; Richard G. Novy; Neil C. Gudmestad (American Journal of Potato Research, 2007)

Association between wetland disturbance and biological attributes in floodplain wetlands - Steven R. Chipps; Daniel E. Hubbard; Kent B. Werlin; Neil J. Haugerud; Kipp A. Powell; Jo Thompson; Tom Johnson (Wetlands, 2006)

Environmental changes in an alpine lake (Gossenköllesee, austria) over the last two centuries – the influence of air temperature on biological parameters - Karin A. Koinig; Christian Kamenik; Roland Schmidt; Anna Agustí-Panareda; Peter Appleby; Andrea Lami; Miroslava Prazakova; Neil Rose; Øyvind A. Schnell; Richard Tessadri; Roy Thompson; Roland Psenner (Journal of Paleolimnology, 2002)

Goldrush: A new high quality russet-skinned potato cultivar - Robert H. Johansen; Bryce Farnsworth; Gary A. Secor; Neil C. Gudmestad; Asunta Thompson-Johns; Edna T. Holm (American Journal of Potato Research, 1994)